TESTING GROUP VELOCITY MAPS FOR EURASIA - Cotte N.; Laske G. (My University, 2002)
Group velocity maps for seismic surface waves play an important role in monitoring the Comprehensive Test Ban Treaty so their accuracy is crucial. Group velocity anomalies can be modelled in terms of lateral variations in crustal and shallow mantle structure, the knowledge of which is important for understanding wave propagation and the blockage of regional phases. Accurate group velocity maps are also indispensable tools in attempts to lower the detection threshold for seismic events and to distinguish between explosions and earthquakes. This paper investigates the feasibility of validating existing maps using a relatively small data set of path-averaged group traveltime data. We find that group velocity correction surfaces calculated for two sets of global maps and a set of regional maps in Eurasia exhibit significant differences. We compare our measurements with predictions from these maps and test whether any of these maps is consistent with our data. Large differences between measurements and predictions can occur for selected individual paths across Eurasia and we find that maps resulting from global inversions fit our data best. There are visually only subtle differences between global and regional maps but we speculate that the long-wavelength structure is relatively poorly constrained in the regional maps.